The impact of the post-Bologna reforms on German higher education and the transition of graduates into the labour market - Ertl, H (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2013)
This paper outlines some of the changes that have been initiated by the Bologna process in German higher education. In particular, it provides a discussion of the impact of these changes on the transition of graduates into the world of work. The paper is based on an analysis of recent studies on students who have graduated with the new type of degrees that were introduced as a result of the Bologna agreement. The paper finds that many of the reforms that took place during the 2000s can be traced back to earlier attempts to improve the conditions of researching, teaching and studying in German higher education. It is argued that employers are, on the whole, supportive of the new Bachelor programmes and that the reforms have addressed some of the long-standing demands of employers. However, the answer to the question as to whether Bachelor degrees are enabling graduates to transition successfully into the labour market is far less positive. The data analysed show particular difficulties for Bachelor graduates from universities as compared with graduates from other types of higher education institutions. Many university Bachelor graduates have difficulties in finding permanent graduate employment and to reach adequate positions within the first year of employment.